Numb - Chaffin, Charles (Ascent Audio, 2021)
Discover how to manage this noisy world without it managing you. In Numb, distinguished author Dr. Charles R. Chaffin delivers a fun and evidence-based exploration of how you can devote more attention on what you believe is important while ignoring the distractions that increasingly permeate your life. Using research from cognitive, education, positive, and clinical psychology, the book identifies the sources of noise and distraction in this information age and how we can manage it in all aspects of our lives. You'll learn about: how experiences in technology, from social media to selfies to porn, impact our ability to engage and connect with others; the news we consume and the impact of confirmation bias, filter bubbles, and tribalism; how FOMO and choice overload impact our decision-making; and the power of our attention in all aspects of our daily lives. Perfect for anyone interested in the expanding impact of the information age on our collective psyche, Numb helps empower you to use technology and information not as a destination, but as a tool towards authenticity and empowerment.